A new emulsification-crosslinking technique for preparation of physically crosslinked chitosan microspheres. (July 2020) - Shi, Aiping; Guan, Ying; Zhang, Yongjun
A new emulsification-crosslinking method was developed for the preparation of chitosan microspheres. The new method uses an aqueous alkali–urea solution, instead of the commonly used acidic solvents, to dissolve chitosan. After emulsification, the water-in-oil droplets are solidified by heating, taking advantage of the unique in situ thermal gelling behavior of the alkaline chitosan solution, instead of by crosslinking with a usually toxic crosslinker. The size of the microspheres can be controlled by the concentration of chitosan solution, stirring speed, emulsifier concentration, and the curing temperature. The resulting microspheres are physically crosslinked, instead of chemically crosslinked, and they are ready to dissolve in dilute acetic acid. The resulting chitosan microspheres are non-toxic and can be degraded by lysozyme. Bovine serum albumin, a model protein, can be facilely loaded into the microspheres by adsorption, and then released from the microspheres.